Effects of restriction of forefoot rocker functions by immobilisation of metatarsophalangeal joints on kinematics and kinetics during walking. (December 2021) - Takahashi, Toshiaki; Nagase, Tokiko; Akatsuka, Seiya; Nakanowatari, Tatsuya; Ohtsu, Hajime; Yoshida, Shinya; Makabe, Hitoshi; Ihashi, Kouji; Kanzaki, Hideto
Highlights: Unilateral metatarsophalangeal joints (MPJs) were immobilised by an aluminium sole. MPJs immobilisation resulted in limited ankle plantarflexion and ankle push-off. To compensate for the reduced ankle work, the positive work by hip joints increased. MPJs immobilisation cause a characteristic centre of mass movement during walking. Other joints showed various compensatory motions in response to the immobilisation. Abstract: Objective: This study was conducted to investigate the effects of restriction of forefoot rocker (FFR) functions by immobilisation of unilateral metatarsophalangeal joints (MPJs) on kinematic and kinetic factors during walking. Methods: Eighteen healthy young adults participated in this study. To immobilise the MPJs of the right leg, an aluminium sole plate (AS) was fixed on the sole of the foot. Kinematic and kinetic data were collected while each subject walked at a comfortable speed with the AS and without. Results: In the AS condition, the walking speed and contralateral step length were significantly decreased, and an asymmetrical centre of mass (COM) movement was observed. The range of plantarflexion motion and positive work by the ankle joint were decreased markedly during the late stance of the AS limb. In contrast, maximum hip and knee flexion angles in the swing phase of the AS limb and positive work by the bilateral hip joints over the gait cycle were increased. Conclusions: The results suggested that MPJ immobilisation may result in marked motion limitation of ankle plantarflexion and inhibition of push-off by the ankle joint despite no restrictions on the ankle joint. These changes may interfere with gait speed and a smooth and symmetrical COM shift during walking.